2013
DOI: 10.4014/jmb.1209.09070
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Oxidative Stress Response Induced by Low-Dose Hydrogen Peroxide in Bacillus anthracis

Abstract: Anthrax is a bacterial disease caused by the aerobic sporeforming bacterium Bacillus anthracis, which is an important pathogen owing to its ability to be used as a terror agent. B. anthracis spores can escape phagocytosis and initiate the germination process even in antimicrobial conditions, such as oxidative stress. To analyze the oxidative stress response in B. anthracis and thereby learn how to prevent antimicrobial resistance, we performed protein expression profiling of B. anthracis strain HY1 treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Thus, investigating factors which support the virulence of a pathogen would provide greater insight into the understanding of bacterial physiology for mining new targets for combating infections. Various stresses encountered by the pathogen within the host like iron depletion (Carlson et al, 2009;Cendrowski et al, 2004), oxidative stress (Cybulski et al, 2009;Kim Abbreviations: Pi, inorganic phosphate; PDM, phosphate depleted medium; PBM, phosphate balanced medium; PRM, phosphate repleted medium; BHI, brain heart infusion media; PBS, phosphate buffer saline; MOI, multiplicity of infection; PA, protective antigen; LF, lethal factor; EF, edema factor; DMEM, Dulbecco's modified eagle's medium; MTT, MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide); ELISA, enzyme linked immunosorbent assay; HRP, horse radish peroxidase; CMS, culture media supernatant. et al, 2013), carbon dioxide stress (McKenzie et al, 2014) etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, investigating factors which support the virulence of a pathogen would provide greater insight into the understanding of bacterial physiology for mining new targets for combating infections. Various stresses encountered by the pathogen within the host like iron depletion (Carlson et al, 2009;Cendrowski et al, 2004), oxidative stress (Cybulski et al, 2009;Kim Abbreviations: Pi, inorganic phosphate; PDM, phosphate depleted medium; PBM, phosphate balanced medium; PRM, phosphate repleted medium; BHI, brain heart infusion media; PBS, phosphate buffer saline; MOI, multiplicity of infection; PA, protective antigen; LF, lethal factor; EF, edema factor; DMEM, Dulbecco's modified eagle's medium; MTT, MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide); ELISA, enzyme linked immunosorbent assay; HRP, horse radish peroxidase; CMS, culture media supernatant. et al, 2013), carbon dioxide stress (McKenzie et al, 2014) etc.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, CAT and SOD enzymes showed increased synthesis/activity during UV-B stress, probably to overcome the impacts of UV-B-induced oxidative stress. Over-production of antioxidative enzymes and carotenoid pigments in D. radiodurans and their roles in protecting the ROS-mediated damaging effects have been also reported by different workers [Tian et al, 2007;Kim et al, 2013]. The major goal of this study relates to the identification of differentially formed proteins in D. radiodurans following UV-B exposure.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies show that the mechanisms of WRF growth inhibition by metals are similar to other microbes (Zeng et al, 2012;Zeng et al, 2015;Zhang et al, 2015). Possible mechanisms of inhibition due to metal-induced toxicity may include; (i) alteration in the morphology of fungal mycelium (Errasquın and Vazquez, 2003;Peña-Castro et al, 2004); (ii) inhibition of intracellular and extracellular proteins due to the denaturation of sulfhydryl groups (Hall, 2002;Kiyono et al, 2010); (iii) disruption in the formation of cell wall by inhibiting Ca +2 dependent regulatory pathways which results in enhanced intercellular Ca +2 efflux (Poirier et al, 2008;Zeng et al, 2012); (iv) induction of oxidative stress due to the inactivation of enzymatic and non-enzymatic antioxidants such as thiols and peroxidases (Kim et al, 2013;Zhang et al, 2015); and (v) formation and accumulation of excessive reactive oxygen species (ROS) namely O −2 , OH −1 and H 2 O 2 , causing severe damage to the cell structure (lipids and proteins) and nucleic acid (DNA and mRNA) as well as enzyme inactivation (Chen et al, 2014;Gupta et al, 2016;Zeng et al, 2012). Despite their potential inhibitory effects, ROS at low concentrations plays an important role in cellular signaling systems such as induction of mutagenic response (Valko et al, 2006;Wan et al, 2015).…”
Section: Growth Inhibition Mechanismsmentioning
confidence: 99%